ADSORPSI ANION Cr(VI) OLEH BATU PASIR TERAKTIVASI ASAM DAN TERSALUT Fe2O3 - Gede Widihati, I. A. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 1 Januari 2008)
The research is about adsorption of three sand type (river, black beach, and white beach) wated with Fe2O3 with and without H2SO4 activated Cr(VI) in water. The research covers the determination of surface acidity of sand by acid-base titration method, their specific surface area by blue methylene method, and of the adsorption, equilibrium adsorption isotherm, and adsorption capacities to Cr(VI) by atomic absorption spectrophotometer. The results indicate that activated white beach sand (AA2) has highest surface acidity (0.4741 mmole/g). The highest specific surface area is given by the sand control (A) (30.8969 m2/g), of beach sand is given by white to sand of AA2 (30.1203 m2/g). Adsorption capacity of sand on Cr(VI) increases with H2SO4 activation. Higness capacities is shown by the white beach sand of AA2 (1.0601 mg/g). Free energy adsorption (Go Ads) on Cr(VI) of white beach sand is -15.5053 kJ/mole indicating a weak chemical adsorption.
Keywords: sand, acid activation, Fe2O3-coated, adsorption